Lithium ion secondary battery, positive electrode active material and power-consuming device
By using a mixture of granular and rod-shaped lithium-containing phosphate materials in the positive electrode sheet of the lithium-ion secondary battery, the problem of performance reduction at low temperatures is solved, and higher energy density, capacity retention and power performance are achieved.
Patent Information
- Application Number
- CN202411556363.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Lithium-containing phosphate materials such as lithium iron phosphate materials have low electron conductivity at low temperatures, resulting in a decrease in ion diffusion rate, affecting the energy density, capacity retention rate and power performance under low temperature conditions.
The lithium-containing phosphate material with different morphology in granular and rod-shaped shapes is graded to form a mixture as the positive electrode active material. By adjusting the diffraction peak intensity ratio and carbon coating amount of the material, the compaction density and low-temperature performance of the positive electrode sheet are improved.
The energy density, capacity retention rate and power performance of lithium-ion secondary batteries under low temperature conditions are improved, taking into account the low temperature performance and volume energy density.
Smart Images

Figure CN119092645B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion secondary battery, a positive electrode active material and an electrical device. Background Art
[0002] In recent years, as the application scope of lithium-ion secondary batteries has become more and more extensive, lithium-ion secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. Among them, lithium-containing phosphate batteries such as lithium iron phosphate have achieved great development.
[0003] As the demand for batteries increases, higher requirements are placed on the energy density and low-temperature performance of batteries. However, due to the inherent low electronic conductivity of lithium iron phosphate materials and other lithium-containing phosphate materials, their ion diffusion rate is significantly reduced at low temperatures, which in turn affects the performance under low-temperature conditions, especially the energy density, capacity retention rate and power performance under low-temperature conditions. Summary of the invention
[0004] In order to achieve the above-mentioned objectives, the first aspect of the present application provides a lithium-ion secondary battery, a positive electrode active material and an electrical device having good energy density, capacity retention rate and power performance under low temperature conditions.
[0005] In a first aspect of the present application, a lithium ion secondary battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode film layer; the positive electrode film layer comprises a positive electrode active material, wherein the positive electrode active material comprises a mixture of a first lithium-containing phosphate material in a granular state and a second lithium-containing phosphate material in a rod-shaped state, wherein the first lithium-containing phosphate material and the second lithium-containing phosphate material have a diffraction peak A between 29° and 30° and a diffraction peak B between 25° and 26° in an X-ray diffraction spectrum, and the intensity ratio of the diffraction peak A to the diffraction peak B is 1:1. A / I B ; The second lithium phosphate material satisfies: 1.1≥I A / I B ≥0.95; I of the second lithium-containing phosphate material A / I B Greater than the I of the first lithium-containing phosphate material A / I B ; Both the first lithium-containing phosphate material and the second lithium-containing phosphate material contain a carbon coating layer, and the amount of carbon coating in the first lithium-containing phosphate material is less than the amount of carbon coating in the second lithium-containing phosphate material.
[0006] Thus, the lithium-ion secondary battery of the present application is mainly improved from the positive electrode sheet, specifically, by grading the lithium-containing phosphate materials with different morphologies of granules and rods to obtain a better compacting effect, thereby improving the compaction density of the positive electrode sheet, so as to improve the energy density of the lithium-ion secondary battery; in addition, the second lithium-containing phosphate material used has a diffraction peak at a specific position, and the intensity ratio of the diffraction peak A to the diffraction peak B is limited to I A / I B , and controlling the difference in carbon coating amount between the first lithium-containing phosphate material and the second lithium-containing phosphate material and I A / I B The difference can improve the low-temperature performance of lithium-ion secondary batteries, while taking into account good energy density, capacity retention and power performance under low-temperature conditions.
[0007] In some embodiments, in the positive electrode active material, the mass content of the first lithium-containing phosphate material is greater than or equal to the mass content of the second lithium-containing phosphate material.
[0008] In some of the embodiments, the mass content of the second lithium-containing phosphate material is 5%-50% in the total mass of the first lithium-containing phosphate material and the second lithium-containing phosphate material.
[0009] In some embodiments, the mass content of the second lithium-containing phosphate material is 10%-30% in the total mass of the first lithium-containing phosphate material and the second lithium-containing phosphate material.
[0010] As the amount of the second lithium-containing phosphate material increases, the power performance of the battery is improved; but a larger amount of the second lithium-containing phosphate material will affect the energy density; by controlling the mass content of the second lithium-containing phosphate within the above range, it is beneficial to balance the low-temperature performance and volume energy density of the lithium-ion secondary battery, so that the lithium-ion secondary battery has both good low-temperature performance and volume energy density.
[0011] In some embodiments, at least one of the following conditions is met:
[0012] (1) The carbon coating amount in the first lithium-containing phosphate material is 1% to 1.3%;
[0013] (2) The carbon coating amount in the second lithium-containing phosphate material is 1.3% to 1.8%;
[0014] (3) The difference between the carbon coating amount in the second lithium-containing phosphate material and the carbon coating amount in the first lithium-containing phosphate material is 0.1% to 0.8%.
[0015] Controlling the difference in the amount of carbon coating is beneficial to further improving the low-temperature performance of the secondary battery, while taking into account better energy density, capacity retention and power performance under low-temperature conditions.
[0016] In some embodiments, at least one of the following conditions is met:
[0017] (1) The first lithium-containing phosphate material satisfies: 0.92 ≥ I A / I B ≥0.8;
[0018] (2) The second lithium-containing phosphate material satisfies: 1.05 ≥ I A / I B ≥0.95.
[0019] Second lithium phosphate material I A / I B Within this range, it can further improve the low temperature performance of the lithium ion secondary battery.
[0020] In some embodiments, the average primary particle size of the first lithium-containing phosphate material is greater than the average primary particle size of the second lithium-containing phosphate material.
[0021] A larger carbon coating will inhibit the growth of the particle size of the lithium-containing phosphate material, making it difficult to obtain particles with a larger particle size, thereby reducing the compaction density of the first lithium-containing phosphate material, and for the first lithium-containing phosphate material, an increase in the carbon coating amount will reduce its gram capacity, so the coating amount of the first lithium-containing phosphate material with a larger particle size is controlled to be smaller, and the first lithium-containing phosphate material mainly plays a role in providing a high compaction density to improve the energy density of the battery. The average particle size of the primary particles of the second lithium-containing phosphate material is smaller, and the probability of its side reactions is greater, so it is necessary to increase its carbon coating amount, improve the integrity of the carbon coating, reduce the probability of side reactions, and improve the effective capacity and electronic conductivity of the second lithium-containing phosphate material; therefore, the coating amount of the second lithium-containing phosphate material with a smaller particle size is controlled to be larger, and the second lithium-containing phosphate material mainly plays a role in high dynamic performance to improve the power performance of the battery. In this way, the first lithium-containing phosphate material with a larger particle size and a smaller coating amount and the second lithium-containing phosphate material with a smaller particle size and a larger coating amount are mixed and used in combination, so that the lithium-ion secondary battery can take into account better energy density, capacity retention rate and power performance under low temperature conditions.
[0022] In some embodiments, the ratio of the average primary particle size of the first lithium-containing phosphate material to the average primary particle size of the second lithium-containing phosphate material is 3 to 40. By controlling this ratio, the second lithium-containing phosphate material can be better filled in the gaps of the first lithium-containing phosphate material to achieve a better tight stacking effect, and at the same time, it is beneficial for the second lithium-containing phosphate material with a smaller particle size to better play its role in improving the power performance of the battery.
[0023] In some embodiments, the average primary particle size of the first lithium-containing phosphate material is 700 nm to 1500 nm.
[0024] In some embodiments, the average primary particle size of the first lithium-phosphate material is 700 nm to 1200 nm.
[0025] By controlling the average particle size of the primary particles of the first lithium-containing phosphate material within the above range, the first lithium-containing phosphate material and the second lithium-containing phosphate material can better fill each other, achieve better tight stacking, and improve the overall compaction density of the positive electrode film layer, thereby taking into account good power performance, higher capacity retention rate and energy density.
[0026] In some embodiments, the average primary particle size of the second lithium-containing phosphate material is 20 nm to 260 nm.
[0027] In some embodiments, the average primary particle size of the second lithium-containing phosphate material is 80 nm to 160 nm.
[0028] The average particle size of the primary particles of the second lithium-containing phosphate material increases. Since the transmission path between the particles becomes longer, controlling the average particle size of the primary particles of the second lithium-containing phosphate material within the above range can make lithium ions have a good migration rate in the positive electrode active material, which is beneficial for the lithium-ion secondary battery to have good capacity retention rate, power performance and energy density under low temperature conditions. At the same time, combined with the first lithium-containing phosphate material with a larger particle size, the compaction density can be increased to increase the energy density of the battery.
[0029] In some embodiments, the aspect ratio of the second lithium-containing phosphate material is (1.1-3.9):1.
[0030] The aspect ratio of the second lithium-containing phosphate material is controlled within the above range, so that the rod-shaped lithium-containing phosphate material in the second lithium-containing phosphate material is mainly short rod-shaped, which can provide a better exposure effect of the (010) crystal plane, which is beneficial to better low-temperature performance. In addition, the aspect ratio within the above range makes its specific surface area within a suitable range, which is beneficial to controlling side reactions and improving battery life. In addition, the upper limit of the aspect ratio is further controlled to control the compaction density of the positive electrode plate within a suitable range, which is beneficial to improving the energy density of the battery.
[0031] In some embodiments, at least one of the following conditions is met:
[0032] (1) The powder compaction density of the first lithium-containing phosphate material under a pressure of 3t is 2.38 g / cm 3 ~2.68 g / cm 3 ;
[0033] (2) The powder compaction density of the second lithium-containing phosphate material under a pressure of 3t is 1.85 g / cm 3 ~2.35 g / cm 3 ;
[0034] (3) The compaction density of the positive electrode film layer on one side of the positive electrode sheet is 2.45 g / cm 3 ~2.8g / cm 3 .
[0035] In some embodiments, the chemical formula of the lithium-containing phosphate in the first lithium-containing phosphate material and the second lithium-containing phosphate material is Li β Fe α M (1-α) PO4, wherein 0.2≤α≤1, 1≤β≤1.1, and M includes at least one of Ti, V, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, and Sr.
[0036] In some of the embodiments, in the positive electrode film layer, the total mass content of the positive electrode active material is 92% to 98%.
[0037] In some embodiments, the positive electrode film layer further includes a binder, and the positive electrode film layer satisfies at least one of the following characteristics:
[0038] (1) In the positive electrode film layer, the mass content of the binder is 1% to 4%;
[0039] (2) The binder includes at least one of polyvinylidene fluoride, polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyurethane, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0040] In some embodiments, the positive electrode film layer further includes a conductive agent, and the positive electrode film layer satisfies at least one of the following characteristics:
[0041] (1) In the positive electrode film layer, the mass content of the conductive agent is 1% to 4%;
[0042] (2) The conductive agent includes at least one of carbon nanotubes, conductive carbon, graphite, acetylene black, metal fibers, organic conductive polymers, graphene, carbon black, Ketjen black, carbon dots and carbon nanofibers.
[0043] In some embodiments, the lithium-ion secondary battery further includes an electrolyte, the electrolyte includes an additive, and the additive includes at least one of 1-methyl-3-[(3-trimethoxysilyl)-propyl]imidazole bis(trifluoromethanesulfonamide), 1-methyl-3-propylpyrrolidine bis(trifluoromethanesulfonic acid)imide grafted with aluminum oxide, lithium difluorobisoxalate borate, fluoroethylene carbonate, and 1,3-dioxolane. The electrolyte contains these additives to improve the low-temperature performance of the battery.
[0044] In a second aspect of the present application, a positive electrode active material is provided, wherein the positive electrode active material comprises a mixture of a first lithium-containing phosphate material containing particles and a second lithium-containing phosphate material containing rods, wherein the first lithium-containing phosphate material and the second lithium-containing phosphate material have a diffraction peak A between 29° and 30° and a diffraction peak B between 25° and 26° in an X-ray diffraction spectrum, and the intensity ratio of the diffraction peak A to the diffraction peak B is 1:1. A / I B ; The second lithium phosphate material satisfies: 1.1≥I A / I B ≥0.95; I of the second lithium-containing phosphate material A / I B Greater than the I of the first lithium-containing phosphate material A / I B ; Both the first lithium-containing phosphate material and the second lithium-containing phosphate material contain a carbon coating layer, and the amount of carbon coating in the first lithium-containing phosphate material is less than the amount of carbon coating in the second lithium-containing phosphate material.
[0045] In some embodiments, the positive electrode active material is the positive electrode active material in the lithium ion secondary battery provided in the first aspect of the present application.
[0046] In a third aspect of the present application, there is provided an electrical device comprising the lithium-ion secondary battery provided in the first aspect of the present application and at least one of the positive electrode active materials provided in the second aspect of the present application.
[0047] The electric device of the present application includes the lithium ion secondary battery provided by the present application, and thus has at least the same advantages as the lithium ion secondary battery.
[0048] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0050] Figure 1 Schematic diagram of a lithium-ion secondary battery according to one embodiment of the present application.
[0051] Figure 2 yes Figure 1 An exploded view of a lithium-ion secondary battery according to an embodiment of the present application is shown.
[0052] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0053] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0054] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0055] Figure 6 Schematic diagram of an electrical device using a lithium-ion secondary battery according to an embodiment of the present application as a power source.
[0056] Figure 7 3 is a SEM image of the first lithium-containing phosphate material and the second lithium-containing phosphate material in Example 1.
[0057] Figure 8 This is the XRD diagram of the second lithium-containing phosphate material prepared in Example 1 of the present application.
[0058] Fig. 9 yes Figure 8Magnified view at diffraction angle 2Theta between 24° and 31°.
[0059] Description of reference numerals:
[0060] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module; 5. Battery cell; 51. Shell; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION
[0061] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0062] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0063] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0064] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0065] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0066] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0067] In this application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A includes not only a1, a2 and a3, but also other members".
[0068] In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0069] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0070] As described in the background technology, with the increasing demand for batteries, higher requirements are put forward for the energy density and low temperature performance of batteries. However, due to the inherent low electronic conductivity of lithium iron phosphate materials and other lithium-containing phosphate materials, their ion diffusion rate is significantly reduced at low temperatures, which in turn affects the performance under low temperature conditions, especially the energy density, capacity retention rate and power performance under low temperature conditions.
[0071] Therefore, how to improve the energy density, capacity retention and power performance of lithium-ion secondary batteries under low temperature conditions is an urgent problem to be solved.
[0072] Based on this, an embodiment of the present application provides a lithium ion secondary battery, a positive electrode sheet, a positive electrode active material and an electric device. The positive electrode sheet and the positive electrode active material will be described in detail below in conjunction with the lithium ion secondary battery.
[0073] An embodiment of the present application provides a lithium-ion secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode film layer; the positive electrode film layer comprises a positive electrode active material, and the positive electrode active material comprises a mixture of a first lithium-containing phosphate material in a granular form and a second lithium-containing phosphate material in a rod-shaped form. In other words, the first lithium-containing phosphate material comprises a lithium-containing phosphate material in a granular form; and the second lithium-containing phosphate material comprises a lithium-containing phosphate material in a rod-shaped form.
[0074] The first lithium-containing phosphate material and the second lithium-containing phosphate material have a diffraction peak A between 29° and 30° and a diffraction peak B between 25° and 26° in the X-ray diffraction spectrum, and the intensity ratio of the diffraction peak A to the diffraction peak B is 1:1. A / I B The second lithium-containing phosphate material satisfies: 1.1≥I A / I B ≥0.95. I of the second lithium-containing phosphate material A / I B Greater than the I of the first lithium-containing phosphate material A / I B .
[0075] The first lithium-containing phosphate material and the second lithium-containing phosphate material both contain a carbon coating layer, and the carbon coating amount in the first lithium-containing phosphate material is less than the carbon coating amount in the second lithium-containing phosphate material.
[0076] Taking lithium iron phosphate as an example, the lithium phosphate material contains a diffraction peak A between 29° and 30° in the X-ray diffraction spectrum. The diffraction peak A corresponds to the (010) crystal plane of the lithium iron phosphate material. Peak A and peak B are the two main peaks of the lithium iron phosphate material. The intensity ratio of peak A (010) can indirectly represent the exposure ratio of the (010) crystal plane. Further, in the present application, the first lithium iron phosphate material containing particles IA / I B In the range of 0.8 to 0.92, as an example, the I of the first lithium iron phosphate material A / I B It can be 0.8, 0.82, 0.85, 0.86, 0.88, 0.89, 0.9, 0.91, 0.92, or within the range consisting of any two of the above point values as end values.
[0077] By controlling the intensity ratio of the diffraction peak of the second lithium-containing phosphate material in the X-ray diffraction spectrum A / I B In the above range, the exposure ratio of the (010) crystal plane of the second lithium-containing phosphate material can be adjusted, thereby adjusting the electrochemical reaction kinetics of the second lithium-containing phosphate material. A / I B The higher the (010) crystal plane exposure ratio of the second lithium-containing phosphate material, the higher the exposure ratio. It is speculated that this may be because during the electrochemical reaction, lithium ions undergo insertion and extraction reactions along the b-axis in the second lithium-containing phosphate material. Therefore, the higher the (010) crystal plane exposure ratio, the more conducive it is to improving the electrochemical reaction kinetics, thereby making the second lithium-containing phosphate material exhibit excellent low-temperature performance when used in lithium-ion secondary batteries.
[0078] At the same time, the carbon coating amount of the second lithium-containing phosphate material is controlled to be relatively large, and the electronic conductivity of the second lithium-containing phosphate material is further improved, which is beneficial to improving its power performance. At the same time, its coating amount can be increased, the coating integrity can be improved, and the side reaction of the second lithium-containing phosphate material can be reduced. The consumption of the active component of the second lithium-containing phosphate material can be reduced, which is beneficial to improving the capacity retention rate of the battery; the I of the first lithium-containing phosphate material A / I B Less than I of the second lithium-containing phosphate material A / I B , which is beneficial to improve the compaction density of the first lithium-containing phosphate material, while more carbon has an adverse effect on the compaction density of the first lithium-containing phosphate material, and more carbon will affect the gram capacity of the first lithium-containing phosphate material; therefore, the carbon coating amount in the first lithium-containing phosphate material is less than the carbon coating amount in the second lithium-containing phosphate material, which is beneficial to improve the energy density, capacity retention rate and power performance of the lithium-ion secondary battery under low temperature conditions.
[0079] Thus, the lithium-ion secondary battery of the present application is mainly improved from the positive electrode sheet, specifically, a good close packing effect is obtained by grading lithium-containing phosphate materials with different morphologies of granular and rod-shaped, thereby improving the compaction density of the positive electrode sheet, so as to improve the energy density of the lithium-ion secondary battery; in addition, the second lithium-containing phosphate material used has a specific intensity ratio of diffraction peak A to diffraction peak B.A / I B , and controlling the difference in carbon coating amount between the first lithium-containing phosphate material and the second lithium-containing phosphate material and I A / I B The difference can improve the low-temperature performance of lithium-ion secondary batteries, while taking into account good energy density, capacity retention and power performance under low-temperature conditions.
[0080] In some embodiments, the difference between the carbon coating amount in the second lithium-containing phosphate material and the carbon coating amount in the first lithium-containing phosphate material is 0.1% to 0.8%; as an example, the difference is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, or within the range of any two of the above point values as end values; further, it can be 0.3% to 0.8%; further, it can be 0.5% to 0.8%. Controlling the difference in the carbon coating amount is beneficial to further improve the low-temperature performance of the secondary battery, taking into account the better energy density, capacity retention rate and power performance under low temperature conditions.
[0081] In some of the embodiments, the carbon coating amount of the first lithium phosphate-containing material is 1% to 1.3%; as an example, the carbon coating amount of the first lithium phosphate-containing material can be 1%, 1.1%, 1.2%, 1.3%, or within a range consisting of any two of the above point values as end values.
[0082] In some of the embodiments, the carbon coating amount of the second lithium phosphate-containing material is 1.3%~1.8%; as an example, the carbon coating amount of the second lithium phosphate-containing material can be 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, or within a range consisting of any two of the above point values as end values.
[0083] The following test methods can be used to qualitatively and quantitatively test the positive electrode active materials in the positive electrode sheets of lithium-ion secondary batteries:
[0084] 1) Battery disassembly
[0085] a. Fully discharge the battery until the voltage reaches 2.0 V;
[0086] b. Then disassemble the battery in the glove box and control the humidity in the glove box to less than 2%;
[0087] c. Separate the positive electrode from the battery, then soak and fully wash off the electrolyte on the positive electrode with DMC (dimethyl carbonate);
[0088] d. Take out the positive electrode and place it in a vacuum drying oven and dry it at 80°C for 5 h.
[0089] 2) Separation of positive electrode active materials
[0090] a. Separating the positive electrode film layer and the positive electrode current collector of the dried positive electrode sheet;
[0091] b. The separated positive electrode film layer was ground into a powder and dissolved in NMP (N-methylpyrrolidone) under heating conditions, and then filtered and the residue was collected, and the dissolution and filtration steps were repeated until the binder was fully removed;
[0092] c. Filter and dry the mixture after fully washing away the binder.
[0093] 3) Conductive agent separation
[0094] The dried mixture powder is dispersed in a liquid medium (the density of the liquid medium is greater than 1.2 g / cm 3 , such as nitrobenzene, bromobenzene or carbon tetrachloride, etc.), and stirred to make it uniformly and basically uniformly mixed. After standing for a long enough time, the solution is separated into layers, the upper layer is a conductive agent such as conductive carbon, and the lower layer is a positive electrode active material.
[0095] 4) Separation of the first lithium-containing phosphate material and the second lithium-containing phosphate material
[0096] Principle: Since the density difference between the first lithium-containing phosphate material and the second lithium-containing phosphate material is small, the two cannot be separated by the density difference; when separating the first lithium-containing phosphate material and the second lithium-containing phosphate material, it is necessary to further utilize the difference in surface wettability between the two: the carbon coating amount of the first lithium-containing phosphate material is less than the carbon coating amount of the second lithium-containing phosphate material, so the hydrophilicity of the first lithium-containing phosphate material is greater than that of the second lithium-containing phosphate material; therefore, bubble flotation is used for separation in a hydrophilic liquid medium, the first lithium-containing phosphate material has a greater hydrophilicity and is easier to precipitate, and the second lithium-containing phosphate material has a less hydrophilicity and is floated.
[0097] Specific steps:
[0098] a. The positive electrode active material in step 3) is dried to obtain a mixture powder;
[0099] b. Similar to the coal screening process, select a suitable hydrophilic liquid medium (such as water, ethylene glycol or propylene glycol, etc.) and a suitable flotation agent (such as fat oil 190), and use bubble flotation method for separation.
[0100] The specific steps are: take 1 kg of the mixed positive electrode material in a liquid medium, adjust it to a more appropriate solid content, add a flotation agent, stir to generate bubbles, collect the floating foam, wash and dry it, and then you can get the second lithium-containing phosphate material; collect the slurry at the bottom, wash and dry it, and then you can get the first lithium-containing phosphate material.
[0101] c. Dry the separated first lithium-phosphate-containing material and the second lithium-phosphate-containing material separately, and perform subsequent characterization analysis on them respectively.
[0102] 5) Conducting I on the second lithium-containing phosphate material A / I B Detection method:
[0103] A certain amount of the separated second lithium-containing phosphate material is weighed, and the diffraction peak intensity ratio of the second lithium-containing phosphate material is tested by X-ray. The second lithium-containing phosphate material is placed on the test platform of the X-ray diffractometer (model Shimadzu XRD-7000) using a copper target X-ray diffractometer. The starting angle of the scan is 10°, the ending angle is 90°, and the step length is 0.013. Then the test is started to obtain a diffraction pattern of the second lithium-containing phosphate material in the range of diffraction angles of 10° to 90°. The intensity ratio I of the diffraction peak is determined according to the diffraction pattern. A / I B .
[0104] Then, the separated first lithium-containing phosphate material and the second lithium-containing phosphate material are respectively subjected to ICP testing with reference to GB / T 33822-2017 to obtain their respective carbon coating amounts.
[0105] As an example, the intensity ratio of the diffraction peak A to the diffraction peak B of the second lithium-containing phosphate material is A / I B It can be 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.06, 1.08, 1.1, or a range consisting of any two of the above point values as end values. Further, I A / I B Satisfaction: I A / I B ≥0.96; further, I A / I B ≥0.98.
[0106] In some embodiments, the intensity ratio of the diffraction peak A to the diffraction peak B of the second lithium-containing phosphate material is A / I B Satisfy: 1.1≥I A / I B ≥0.95; further, 1.05≥I A / I B ≥0.95; further, 1.05≥I A / I B ≥0.96. Within this range, it can further improve the low temperature performance of lithium-ion secondary batteries.
[0107] The first lithium-containing phosphate material and the second lithium-containing phosphate material of the present application can be purchased commercially. The present application has no particular limitation on the preparation method of the second lithium-containing phosphate material, as long as the purpose of the present application can be achieved.
[0108] In some embodiments, the second lithium-containing phosphate material can be prepared by liquid phase synthesis, taking lithium iron phosphate as an example, which includes the following steps:
[0109] Step A: Mix an iron source, a lithium source and a phosphorus source in a certain proportion, add a solvent and mix to obtain a mixed solution A.
[0110] Further, the solvent is selected from alcohol, water or a mixed solvent of alcohol and water. Further, the alcohol is selected from one of ethanol, methanol, ethylene glycol and propylene glycol. Further, the iron source includes but is not limited to at least one of divalent iron salts such as ferrous sulfate, ferrous chloride, ferrous acetate and ferrous oxalate. Further, the phosphorus source includes but is not limited to at least one of phosphoric acid, diammonium phosphate, (NH4)2HPO4, LiH2PO4, Li3PO4 and (NH4)3PO4. Further, the lithium source includes but is not limited to at least one of lithium hydroxide, lithium oxide, lithium chloride, lithium nitrite, lithium nitrate, lithium oxalate, lithium carbonate, lithium acetate, lithium phosphate, lithium dihydrogen phosphate and lithium hydrogen phosphate.
[0111] Furthermore, the amounts of the iron source, lithium source and phosphorus source added are based on a molar concentration ratio of 0.5 mol: 0.65 mol: 1.5 mol of iron atoms, phosphorus atoms and lithium atoms.
[0112] Step B: After adding a surfactant to the mixed solution A, a pH adjuster is added to adjust the pH of the mixed solution A to 7-8 to obtain a mixed solution B.
[0113] The surfactant includes but is not limited to at least one of sodium citrate, sodium lactate, sodium malate and sodium tartrate. Further, as an example, the mass ratio of the surfactant to the mixed solution A is 1:100.
[0114] Step C: Transfer the mixed solution B to a reactor, seal it and react it at a temperature of 170°C to 250°C for 1 h to 6 h. After cooling, filter and wash the precipitate obtained by the reaction to obtain a lithium iron phosphate material.
[0115] During the hydrothermal precipitation process, the (010) crystal plane of lithium iron phosphate exposes more iron ions. Due to the coordination effect of the surfactant, they are adsorbed on the (010) surface, limiting the further growth rate of the (010) plane and reducing the thickness in the (010) crystal direction. The energy required for the lithium ion deintercalation reaction along the (010) crystal direction is the lowest, which can significantly improve the transmission speed of lithium ions and reduce the diffusion impedance of the solid-phase reaction.
[0116] Furthermore, the method may further include step D: drying the lithium iron phosphate material obtained in step C, uniformly mixing it with a carbon source, and then sintering and carbonizing it in a nitrogen inert atmosphere to obtain a carbon-coated lithium iron phosphate material.
[0117] Furthermore, the carbon source includes but is not limited to at least one of glucose, sucrose, starch, and polyethylene glycol. Furthermore, the sintering carbonization temperature is 750° C. to 800° C. Furthermore, the mass ratio of the lithium iron phosphate material obtained in step C to the carbon source is 20:1.
[0118] In the present application, the intensity ratio I of the diffraction peak can be adjusted by controlling the hydrothermal reaction time t in step C, the concentration C of the hydrothermal reactant in step C, the concentration Cx of the surfactant added to the hydrothermal reactant in step C, or the selection of the surfactant. A / I B The applicant found that as the reaction time increases, A / I B The value keeps increasing, but when the reaction time continues to increase, I A / I B The value will show a downward trend. Based on this, the liquid phase reaction time is regulated to be 1 h to 6 h in this application. Within this reaction time range, I A / I B The value increases with the extension of the reaction time. The synthesis process of the first granular lithium-containing phosphate material and the second lithium-containing phosphate material is different. The second lithium-containing phosphate material is prepared by a liquid phase reaction method to facilitate better adjustment of the crystal surface exposure ratio, that is, I A / I B .
[0119] In some of the embodiments, in the positive electrode active material, the mass content of the first lithium-containing phosphate material is greater than or equal to the mass content of the second lithium-containing phosphate material.
[0120] In some embodiments, the mass content of the second lithium-containing phosphate material is 5% to 50% of the total mass of the first lithium-containing phosphate material and the second lithium-containing phosphate material, and may further be 10% to 30%. As an example, the mass content may be 5%, 8%, 10%, 12%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or a range consisting of any two of the above point values as end values.
[0121] As the amount of the second lithium-containing phosphate material increases, the power performance of the battery is improved; but a larger amount of the second lithium-containing phosphate material will affect the energy density; by controlling the mass content of the second lithium-containing phosphate material within the above range, it is beneficial to balance the low-temperature performance and volume energy density of the lithium-ion secondary battery, so that the lithium-ion secondary battery has both good low-temperature performance and volume energy density.
[0122] For the total mass of the first lithium-containing phosphate material and the second lithium-containing phosphate material in the positive electrode sheet of the battery, the mass content of the second lithium-containing phosphate material can be detected by the following method:
[0123] The first lithium-containing phosphate material and the second lithium-containing phosphate material are separated by using steps 1) to 4) in the above-mentioned qualitative and quantitative test of the positive electrode active material in the positive electrode sheet of the lithium-ion secondary battery, and are weighed to obtain their respective masses. In this way, the mass ratio of the first lithium-containing phosphate material and the second lithium-containing phosphate material in the positive electrode sheet can be obtained.
[0124] The primary average particle size refers to the average particle size of the primary particles. The primary particles in this application do not have obvious agglomeration interfaces in the particle cross-section diagram, but may have tiny pores and point and line defects. Among them, the "primary average particle size" refers to the average value of the primary particle sizes of all particles, which is numerically equal to the total particle size value divided by the total number of particles.
[0125] In some of the embodiments, the average primary particle size of the first lithium-containing phosphate material is greater than the average primary particle size of the second lithium-containing phosphate material.
[0126] A larger carbon coating will inhibit the growth of the particle size of the lithium-containing phosphate material, making it difficult to obtain particles with a larger particle size, thereby reducing the compaction density of the first lithium-containing phosphate material, and for the first lithium-containing phosphate material, an increase in the carbon coating amount will reduce its gram capacity, so the coating amount of the first lithium-containing phosphate material with a larger particle size is controlled to be smaller, and the first lithium-containing phosphate material mainly plays a role in providing a high compaction density to improve the energy density of the battery. The average particle size of the primary particles of the second lithium-containing phosphate material is smaller, and the probability of its side reactions is greater, so it is necessary to increase its carbon coating amount, improve the integrity of the carbon coating, reduce the probability of side reactions, and improve the effective capacity and electronic conductivity of the second lithium-containing phosphate material; therefore, the coating amount of the second lithium-containing phosphate material with a smaller particle size is controlled to be larger, and the second lithium-containing phosphate material mainly plays a role in high dynamic performance to improve the power performance of the battery. In this way, the first lithium-containing phosphate material with a larger particle size and a smaller coating amount and the second lithium-containing phosphate material with a smaller particle size and a larger coating amount are mixed and used in combination, so that the lithium-ion secondary battery can take into account better energy density, capacity retention rate and power performance under low temperature conditions.
[0127] Further, the ratio of the average primary particle size of the first lithium-containing phosphate material to the average primary particle size of the second lithium-containing phosphate material is 3 to 40, and as an example, it can be 3, 3.1, 3.5, 4, 5, 6, 7, 8, 8.5, 8.75, 9, 10, 12, 15, 16, 17, 18, 18.75, 19, 20, 25, 30, 35, 40, or in the range formed by any two of the above point values as end values; it can be selected from 5 to 15, and further can be 5 to 10. By controlling this ratio, the second lithium-containing phosphate material can be better filled in the gap of the first lithium-containing phosphate material to achieve a better close stacking effect, and at the same time, it is beneficial for the second lithium-containing phosphate material with a smaller particle size to better play its role in improving the power performance of the battery.
[0128] In some embodiments, the average primary particle size of the first lithium-containing phosphate material is 700nm-1500nm. For example, the average primary particle size of the first lithium-containing phosphate material is 700nm, 750nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, or a range consisting of any two of the above point values as end values. Further, the average primary particle size of the first lithium-containing phosphate material can be 700nm-1200nm.
[0129] By controlling the average particle size of the primary particles of the first lithium-containing phosphate material within the above range, the first lithium-containing phosphate material and the second lithium-containing phosphate material can better fill each other, achieve better tight stacking, and improve the overall compaction density of the positive electrode film layer, thereby taking into account good power performance, higher capacity retention rate and energy density.
[0130] In some embodiments, the primary particle size distribution range of the first lithium-containing phosphate material is 600 nm to 3000 nm. The particle size distribution range refers to the interval from the minimum to the maximum value of the particle size in the material, and this range reflects the overall span of the particle size in the material.
[0131] In some embodiments, the average particle size of the primary particles of the second lithium-containing phosphate material is 20nm~260nm. As an example, the average particle size of the primary particles of the second lithium-containing phosphate material is 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 180nm, 200nm, 210nm, 220nm, 240nm, 250nm, 260nm, or within the range formed by any two of the above point values as end values. Further, the average particle size of the primary particles of the second lithium-containing phosphate material can be 80nm~160nm.
[0132] The average particle size of the primary particles of the second lithium-containing phosphate material increases. Since the transmission path between the particles becomes longer, controlling the average particle size of the primary particles of the second lithium-containing phosphate material within the above range can make lithium ions have a good migration rate in the positive electrode active material, which is beneficial for the lithium-ion secondary battery to have good capacity retention rate, power performance and energy density under low temperature conditions. At the same time, combined with the first lithium-containing phosphate material with a larger particle size, the compaction density can be increased to increase the energy density of the battery.
[0133] In some embodiments, the aspect ratio of the second lithium-containing phosphate material is (1.1-3.9):1. As an example, the aspect ratio can be 1.1:1, 1.2:1, 1.4:1, 1.5:1, 1.8:1, 2:1, 2.5:1, 2.6:1, 3:1, 3.5:1, 3.6:1, 3.9:1, or a range consisting of any two of the above point values as end values. Further, the aspect ratio of the second lithium-containing phosphate material is (1.5-2.6):1. The aspect ratio of the second lithium-containing phosphate material is controlled within the above range, so that the rod-shaped lithium-containing phosphate material in the second lithium-containing phosphate material is mainly short rod-shaped, which can provide a better exposure effect of the (010) crystal plane, which is beneficial to better low-temperature performance. In addition, the aspect ratio within the above range makes its specific surface area within a suitable range, which is beneficial to controlling side reactions and improving battery life. In addition, the upper limit of the aspect ratio is further controlled to control the compaction density of the positive electrode plate within a suitable range, which is beneficial to improving the energy density of the battery.
[0134] It is to be understood that the granular shape includes one or more of a spherical shape and a spheroidal shape.
[0135] The average primary particle size of the first lithium-containing phosphate material and the average primary particle size of the second lithium-containing phosphate material in the positive electrode sheet, as well as the aspect ratio of the second lithium-containing phosphate material, can be detected by the following method.
[0136] The positive electrode sheet is cut open perpendicularly to the large surface of the positive electrode sheet using an argon ion beam to expose the cross section, which is photographed using a scanning electron microscope. The particle size of the lithium-containing phosphate material is statistically analyzed using a long diameter statistical method (the long diameter is used as the primary particle size). Specifically, the total number of lithium-containing phosphate primary particles and the sum of the primary particle sizes of the lithium-containing phosphate primary particles can be counted in the scanning electron microscope photograph. The primary average particle size of the lithium-containing phosphate material particles = the primary particle size of the total lithium-containing phosphate material / the total number of lithium-containing phosphate materials.
[0137] In the above process, the total number of lithium-containing phosphate particles with a primary particle size greater than 600 nm in the scanning electron microscope photograph and the sum of the primary particle sizes of the lithium-containing phosphate particles with a primary particle size greater than 600 nm are counted separately, that is, the total number of the first lithium-containing phosphate particles and the sum of the primary particle sizes; the primary average particle size of the first lithium-containing phosphate material particles = the sum of the primary particle sizes of the first lithium-containing phosphate material / the total number of the first lithium-containing phosphate material.
[0138] In the above process, the total number of lithium-containing phosphate particles with a primary particle size less than or equal to 600 nm and the sum of the primary particle sizes of the lithium-containing phosphate particles with a primary particle size less than or equal to 600 nm are counted separately, that is, the total number of the second lithium-containing phosphate particles and the sum of the primary particle sizes; the primary average particle size of the second lithium-containing phosphate material particles = the sum of the primary particle sizes of the second lithium-containing phosphate material / the total number of the second lithium-containing phosphate material.
[0139] In the above process, when the particle size of the lithium-containing phosphate material is statistically analyzed by the length-diameter statistical method, the long diameter a and the short diameter b of each particle are measured, and their ratio, i.e., the aspect ratio of the particle, is obtained; the first lithium-containing phosphate material and the second lithium-containing phosphate material can be intuitively detected and distinguished.
[0140] In some embodiments, the first lithium-containing phosphate material has a powder compaction density of 2.38 g / cm2 at a pressure of 3 t. 3 ~2.68 g / cm 3 In some embodiments, the second lithium-phosphate material has a powder compaction density of 1.85 g / cm2 at a pressure of 3 t. 3 ~2.35 g / cm 3 .
[0141] In some embodiments, the compaction density of the positive electrode film layer on one side of the positive electrode sheet is 2.45 g / cm 3 ~2.8g / cm 3 .
[0142] In this application, the pole piece compaction density test method is:
[0143] When the pole piece is coated on one side, the compaction density of the film layer on one side of the pole piece = m / (V1-V2); when the pole piece is coated on both sides, the compaction density of the film layer on one side of the pole piece = m / [2×(V1-V2)], where m represents the weight of the film layer, V1 represents the volume of the pole piece, and V2 represents the volume of the current collector. m can be obtained by subtracting the weight of the current collector from the weight of the pole piece. The product of the surface area of the pole piece and the thickness of the pole piece is the volume V1 of the pole piece, and the product of the surface area of the pole piece and the thickness of the current collector is V2. The thickness of the current collector and the thickness of the pole piece are obtained by measuring the thickness of the empty foil in the pole lug area and the thickness of the film area with a micrometer.
[0144] In some embodiments, the chemical formula of the lithium-containing phosphate in the first lithium-containing phosphate material and the second lithium-containing phosphate material is Li β Fe α M (1-α) PO4, wherein 0.2≤α≤1, 1≤β≤1.1, and M is a doping metal element, including but not limited to at least one of Ti, V, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, and Sr. It is understandable that the specific types of the lithium-containing phosphate in the first lithium-containing phosphate material and the second lithium-containing phosphate material may be the same or different.
[0145] The lithium-containing phosphate includes doped or undoped lithium iron phosphate. As an example, the first lithium-containing phosphate material and the second lithium-containing phosphate material may include at least one of undoped lithium iron phosphate (LiFePO4), lithium iron manganese phosphate, lithium iron cobalt phosphate, and lithium iron nickel phosphate.
[0146] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode active material is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode active material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode active material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode active materials is also within the scope of positive electrode active materials. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode active material, and non-limiting examples include coating modification.
[0147] In the list of positive electrode active materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.
[0148] In some of the embodiments, in the positive electrode film layer, the total mass content of the positive electrode active material is 92%~98%. As an example, it can be 92%, 93%, 94%, 95%, 96%, 97%, 98%, or within the range consisting of any two of the above point values as end values.
[0149] Furthermore, the positive electrode film layer also includes a binder. Further, in the positive electrode film layer, the mass content of the binder is 1% to 4%, and as an example, it can be 1%, 2%, 3%, 4%, or within the range formed by any two of the above point values as end values.
[0150] Furthermore, the binder includes at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol, polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose, polyurethane, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0151] Furthermore, the positive electrode film layer also includes a conductive agent.
[0152] Furthermore, the mass content of the conductive agent is 1% to 4%. As an example, it can be 1%, 2%, 3%, 4%, or within a range consisting of any two of the above point values as end values.
[0153] Further, the conductive agent includes at least one of carbon nanotubes, conductive carbon, graphite, acetylene black, metal fibers, organic conductive polymers, graphene, carbon black, Ketjen black, carbon dots and carbon nanofibers, wherein the carbon nanofibers include but are not limited to gas-phase carbon nanofibers.
[0154] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000mPa·s~25000mPa·s. When the positive electrode slurry is coated, the coating unit surface density on a dry weight basis (excluding the solvent) can be 15mg / cm 2 ~35mg / cm 2 .
[0155] It is understandable that another embodiment of the present application further provides a method for preparing the above-mentioned lithium-ion secondary battery, which includes the step of forming the above-mentioned positive electrode plate.
[0156] The positive electrode sheet includes not only the positive electrode film layer mentioned above, but also a positive electrode current collector. The positive electrode film layer is disposed on at least one surface of the positive electrode current collector.
[0157] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0158] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0159] Generally, lithium-ion secondary batteries include a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet and the negative electrode sheet are arranged opposite to each other, and the separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows ions to pass through.
[0160] Negative electrode
[0161] The negative electrode plate includes a negative electrode current collector. Further, the negative electrode plate may also include a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0162] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0163] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0164] In some of the embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0165] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0166] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0167] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0168] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000~10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75~220 g / m 2 The compaction density of the negative electrode sheet can be 1.0 g / cm 3 ~ 1.8 g / cm 3 .
[0169] Electrolytes
[0170] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0171] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0172] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0173] In some embodiments, the solvent includes at least one of an ether solvent, an ester solvent and a sulfone solvent.
[0174] As an example, the ether solvent may include at least one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), triethylene glycol dimethyl ether (TRGDME), tetraethylene glycol dimethyl ether (TEGDME), and 1,3-dioxolane (DOL);
[0175] As an example, the ester solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), γ-butyrolactone (BL), 1,3-propane sultone (1,3-PS), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), propyl propionate (PP) and ethyl butyrate (EB). Further, the ester solvent may include ethyl propionate (EP), and ethyl propionate (EP) added to the solvent can improve the low temperature performance.
[0176] As an example, the sulfone-based solvent includes dimethyl sulfoxide (DMSO).
[0177] Furthermore, the solvent includes an ester solvent and an ether solvent.
[0178] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0179] Further, the additive improving low temperature performance may include at least one of an ionic liquid type additive, lithium difluorobis(oxalato)borate (LiODFB), fluoroethylene carbonate (FEC), and 1,3-dioxolane (DOL).
[0180] Furthermore, the ionic liquid additives include but are not limited to at least one of 1-methyl-3-[(3-trimethoxysilyl)-propyl] imidazole bis(trifluoromethanesulfonamide) and 1-methyl-3-propylpyrrolidine bis(trifluoromethanesulfonic acid) imide (Al2O3-PY-TFSI) grafted with aluminum oxide, which can reduce the activation energy of ion transfer, thereby reducing the charge transfer impedance at low temperatures, and can effectively improve the low-temperature performance of lithium-ion secondary batteries, and keep the capacity retention rate of lithium-ion secondary batteries stable at -20°C. Among them, lithium difluorobis(oxalate)borate (LiODFB) can reduce the charge transfer resistance and improve the low-temperature performance. Fluorinated ethylene carbonate (FEC) can reduce the viscosity of the electrolyte, improve the low-temperature conductivity of the electrolyte, and improve the low-temperature capacity and low-temperature power. 1,3-Dioxolane (DOL) has the characteristics of low freezing point and low viscosity, which can reduce the charge transfer impedance of the electrolyte at low temperatures, increase the migration rate of Li ions, and improve the low-temperature performance.
[0181] Isolation film
[0182] In some embodiments, the lithium-ion secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0183] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0184] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may be 12 μm to 20 μm.
[0185] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.
[0186] In some embodiments, the lithium-ion secondary battery may include an outer packaging, which can be used to encapsulate the electrode assembly and the electrolyte.
[0187] In some embodiments, the outer packaging of the lithium-ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium-ion secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0188] Another embodiment of the present application provides an electric device, which includes the lithium-ion secondary battery.
[0189] The lithium ion secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0190] A lithium-ion secondary battery includes at least one battery cell. A lithium-ion secondary battery may include one or more battery cells.
[0191] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0192] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1The lithium-ion secondary battery shown is a battery cell, which is an example of a battery cell of an exemplary square structure.
[0193] In some of the embodiments, the lithium-ion secondary battery may include an outer package. The outer package may be used to encapsulate the electrode assembly and the electrolyte. In some of the embodiments, the outer package of the lithium-ion secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the lithium-ion secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0194] In some of these embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.
[0195] In some embodiments, the lithium-ion secondary battery may be a battery module or a battery pack. The battery module includes at least one battery cell. The number of battery cells contained in the battery module may be one or more, and those skilled in the art may select an appropriate number according to the application and capacity of the battery module.
[0196] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0197] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0198] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.
[0199] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0200] In addition, one embodiment of the present application further provides an electrical device, which includes the above-mentioned lithium-ion secondary battery provided in the present application. The lithium-ion secondary battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited to these. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited to these.
[0201] As an electrical device, a lithium-ion secondary battery can be selected according to its usage requirements.
[0202] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion secondary batteries, a battery pack or a battery module can be used.
[0203] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion secondary battery may be used as a power source.
[0204] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0205] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0206] Example 1
[0207] (1) Preparation of positive electrode
[0208] 1. The first lithium iron phosphate material (granular)
[0209] The first lithium iron phosphate material uses carbon-coated LiFePO4 with an average primary particle size of 800nm, and its particle size distribution is in the range of 600nm~3000nm. The mass content of carbon is 1.1%, and the powder compaction density of the first lithium iron phosphate material under 3t pressure is 2.55 g / cm 3 .
[0210] 2. Preparation of the second lithium iron phosphate material (rod-shaped):
[0211] Step A: Mix ferrous sulfate, lithium hydroxide and phosphoric acid with water in an amount such that the molar concentration ratio of iron atom, phosphorus atom and lithium atom is 0.5 mol: 0.65 mol: 1.5 mol to obtain a mixed solution A.
[0212] Step B: After adding the surfactant sodium citrate to the mixed solution A, the mass ratio of the surfactant to the mixed solution A is 1:100, and then adding a pH adjuster to adjust the pH of the mixed solution A to 7-8, to obtain a mixed solution B.
[0213] Step C: Transfer the mixed solution B to a reaction kettle, seal it and react it at a temperature of 200° C. for 1 h to 6 h. After cooling, filter and wash the precipitate obtained by the reaction to obtain a lithium iron phosphate material.
[0214] Step D: The lithium iron phosphate material obtained in step C is dried and uniformly mixed with carbon source glucose (the mass ratio of lithium iron phosphate material to carbon source is 20:1), and then sintered and carbonized at 800°C in a nitrogen inert atmosphere to obtain carbon-coated LiFePO4, i.e., the second lithium iron phosphate material, whose average primary particle size is 80nm, and whose carbon coating mass content is 1.7%. The second lithium iron phosphate material has a powder compaction density of 2.1g / cm under a pressure of 3t. 3 .
[0215] 3. Preparation of positive electrode
[0216] The first lithium iron phosphate material and the second lithium iron phosphate material are mixed at a mass ratio of 9:1 to form a positive electrode active material.
[0217] The positive electrode active material, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were uniformly mixed in a proper amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 95:3:2 to obtain a positive electrode slurry with a viscosity of 20000 mPa·s.
[0218] The positive electrode slurry was prepared at 280 g / m 2The coating weight is evenly coated on the positive electrode current collector aluminum foil with a thickness of 15μm, and dried at 100℃ to form a positive electrode film layer; the positive electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes; the compaction density of the positive electrode sheet is 2.6g / cm 3 .
[0219] (2) Preparation of negative electrode sheet:
[0220] The negative electrode active material graphite, conductive agent conductive carbon black, binder styrene butadiene rubber and sodium carboxymethyl cellulose were mixed in a mass ratio of 93:3:2:2, deionized water was added as a solvent, and the mixture was stirred under the action of a vacuum stirrer until the system was uniform to obtain a negative electrode slurry with a viscosity of 20000 mPa·s; the obtained negative electrode slurry was heated at 200 g / m 2 The coating weight is evenly coated on the surface of a copper foil with a thickness of 8 μm, dried in an oven at 100°C, and then subjected to processes such as cold pressing, tab forming, and slitting to obtain the negative electrode sheet.
[0221] (3) Isolation film
[0222] A 9μm thick polyethylene isolation film was selected.
[0223] (4) Preparation of electrolyte
[0224] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then the lithium salt LiPF6 is dissolved in the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0225] (5) Preparation of batteries:
[0226] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order and wound by a winding device to obtain a bare battery cell; the electrode assembly is placed in an outer square shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, exhausting and other processes, a lithium-ion secondary battery is finally obtained. The electrolyte injection coefficient is 3.6g / Ah.
[0227] Comparative Examples 1-2 and Examples 2-6
[0228] It is basically the same as Example 1, except that the strength of the second lithium iron phosphate material is A / I B , the average particle size of the primary particles and the aspect ratio are different. The strength ratio of the second lithium iron phosphate material in each embodiment is I A / I B The average particle size of the primary particles and the aspect ratio can be adjusted by adjusting the hydrothermal reaction time in step C. The specific parameters are shown in Table 1.
[0229] Comparative Example 3
[0230] Comparative Example 3 is substantially the same as Example 1, except that the strength of the second lithium iron phosphate material is A / I B As shown in Table 1, it is prepared by solid phase synthesis method and is in the form of spherical particles.
[0231] Embodiments 7 to 10
[0232] It is basically the same as Example 1, except that in the preparation step of the positive electrode plate, the mixing mass ratio of the first lithium iron phosphate and the second lithium iron phosphate is different, so the mass content of the second lithium iron phosphate in the total amount of the first lithium iron phosphate and the second lithium iron phosphate is different, as shown in Table 1.
[0233] Embodiment 11-12
[0234] It is basically the same as Example 1, except that the average particle size of the primary particles of the first lithium iron phosphate material used is different, and its particle size distribution is also in the range of 600nm~3000nm, and the mass content of carbon is the same as that of Example 1; I of the first lithium iron phosphate material in Examples 1, 11~12 is A / I B They are 0.88, 0.89 and 0.85 respectively.
[0235] The parameters are shown in Table 1.
[0236] The following is a performance test.
[0237] (1) Scanning electron microscope (SEM) test.
[0238] The first lithium iron phosphate material and the second lithium iron phosphate material prepared in Example 1 were tested by scanning electron microscope. The results were as follows: Figure 7 As shown in (A) and (B).
[0239] (2) XRD test (X-ray test).
[0240] The carbon-coated lithium iron phosphate material obtained in step D of Example 1 was subjected to XRD detection; specifically, a copper target X-ray diffractometer was used, the material to be detected was placed on the test platform of the X-ray diffractometer (model Shimadzu XRD-7000), the starting angle of the scan was 10°, the ending angle was 90°, the step length was 0.013, and then the test was started to obtain a diffraction pattern of the second active material in the diffraction angle range of 10° to 90°, and the intensity ratio I of the diffraction peak was determined according to the diffraction pattern. A / I B .
[0241] The obtained XRD pattern is as follows: Figure 8 and Fig. 9 As shown, in the X-ray diffraction pattern, there is a diffraction peak A between 29° and 30°, and a diffraction peak B between 25° and 26°, and the intensity ratio of the diffraction peak A to the diffraction peak B is 1 A / I B =0.96.
[0242] (3) -20℃ capacity retention test:
[0243] The lithium ion secondary batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, and then charged to 3.65V at a constant current rate of 0.33C, and then charged to 0.05C at a constant voltage rate of 3.65V. After the charging was completed, the tested batteries were left to stand at 25°C for 2 hours, and then discharged to 2.5V at a DC rate of 0.5C, and the discharge capacity at room temperature was recorded as C0;
[0244] The lithium ion secondary batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, then charged to 3.65V at a constant current rate of 0.33C, and then charged to 0.05C at a constant voltage rate of 3.65V. After charging, the tested batteries were left at -20°C for 2 hours, and then discharged to 2.5V at a DC rate of 0.5C, and the -20°C discharge capacity was recorded as C1. The capacity retention rate of the lithium ion secondary battery at -20°C is: (C1 / C0)×100%.
[0245] (4) -20℃ power performance test:
[0246] Capacity calibration: After the lithium ion secondary batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, they were charged to 3.65V at a constant current of 0.33C, and then charged to 0.05C at a constant voltage of 3.65V. After the charging was completed, the tested batteries were kept at 25°C for 2 hours, and then discharged to 2.5V at a direct current of 0.33C, and the discharge capacity at room temperature was recorded as C0;
[0247] Adjust SOC (state of charge): Keep the lithium-ion secondary battery with calibrated capacity at 25°C for 2 hours, then discharge it at a 1 / 3C0 discharge rate for 144 minutes to adjust the capacity of the lithium-ion secondary battery to 20% SOC;
[0248] Power test: After the 20% SOC lithium-ion secondary battery is left at -20℃ for 2h, it is discharged at a discharge rate of 3C0 for 30s under a pulse current I. The voltage before 3C0 discharge is recorded as V1, and the voltage at the end of 30s discharge is recorded as V2; the value DCR of (V1-V2) / I is calculated, and this data can be used to characterize the power performance of the battery. The smaller the DCR value, the greater the power performance of the battery.
[0249] (5) Volume energy density E at -20℃ x calculate:
[0250] The lithium ion secondary batteries prepared in the examples and comparative examples were kept at 25°C for 2 hours, and then charged to 3.65V at 0.33C constant current, and then charged to 0.05C at 3.65V. After charging, the tested batteries were kept at -20°C for 2 hours, and then discharged to 2.5V at 0.33C DC, and the discharge energy E0 (Wh) of the lithium battery, the coating area S (dm 2 ) and the thickness of the positive electrode h (dm), then the volume energy density E x =E0 / (S×h), unit is Wh / dm 3 .
[0251] Some parameters and performance test results of various embodiments and comparative examples are shown in Table 1.
[0252] Table 1
[0253]
[0254] In Table 1, the first LFP and the second LFP are the first lithium iron phosphate material and the second lithium iron phosphate material, respectively. The mass content of the second LFP refers to the mass content of the second lithium iron phosphate material in the total amount of the first lithium iron phosphate material and the second lithium iron phosphate material.
[0255] In Comparative Example 1, the positive electrode active material of the positive electrode plate only uses the second lithium iron phosphate material, which has good low-temperature capacity retention and low-temperature power performance, but has a low energy density due to its low compaction density. In Comparative Example 2, the positive electrode active material of the positive electrode plate only uses the first lithium iron phosphate material, which has poor low-temperature capacity retention and low-temperature power performance. Therefore, although its plate compaction density is high, the energy density is still reduced.
[0256] Comparative Example 3 uses 1 A / I B The capacity retention rate and energy density of the first lithium iron phosphate material with a lower temperature are improved compared with those of Comparative Example 2, but its DCR value at low temperature is still in a relatively high range, indicating that its improvement in power performance is relatively small.
[0257] Compared with Comparative Examples 1 to 3, the positive electrode active material of the positive electrode plate of each embodiment is a mixture of the first lithium iron phosphate material and the second lithium iron phosphate material, which can take into account good low-temperature capacity retention, low-temperature power performance and energy density.
[0258] It can be seen from Examples 1 to 3 that the second lithium iron phosphate material A / I BThe value increases in the range of 0.95~1.05, and its DCR value at low temperature decreases, indicating that its low-temperature power performance is improved, and the low-temperature capacity retention rate and energy density are also improved. It can be seen from Examples 1 and 4~6 that the average particle size of the primary particles of the second lithium iron phosphate material increases. Since the transmission path between the particles becomes longer, its low-temperature DCR value increases. The aspect ratio of the second lithium iron phosphate material is controlled within a suitable range, so that the rod shape of the second lithium iron phosphate is mainly short rod-shaped, which can provide a better exposure effect of the (010) crystal plane, which is conducive to improving low-temperature performance and obtaining better capacity retention rate and energy density. It can be seen from Examples 1 and 7~10 that as the amount of the second lithium iron phosphate material increases, its low-temperature DCR value decreases, the low-temperature power performance and capacity retention rate are greatly improved, and the energy density first increases and then decreases. This is because the amount of the second lithium iron phosphate material is large, which makes the amount of the first lithium iron phosphate material small, thus resulting in a decrease in energy density. It can be seen from Example 1 and Examples 11-12 that further controlling the average particle size of the primary particles of the first lithium iron phosphate material can take into account a lower low-temperature DCR value (ie, better power performance), a higher capacity retention rate and energy density.
[0259] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0260] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A lithium ion secondary battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode film layer; the positive electrode film layer comprises a positive electrode active material, wherein the positive electrode active material comprises a mixture of a first lithium-containing phosphate material in a granular state and a second lithium-containing phosphate material in a rod-shaped state, wherein the first lithium-containing phosphate material and the second lithium-containing phosphate material have a diffraction peak A between 29° and 30° and a diffraction peak B between 25° and 26° in an X-ray diffraction spectrum, and an intensity ratio of the diffraction peak A to the diffraction peak B is 1:
1. A / I B ; The second lithium phosphate material satisfies: 1.1≥I A / I B ≥0.95; I of the second lithium-containing phosphate material A / I B Greater than the I of the first lithium-containing phosphate material A / I B ; Both the first lithium-containing phosphate material and the second lithium-containing phosphate material contain a carbon coating layer, the carbon coating amount in the first lithium-containing phosphate material is less than the carbon coating amount in the second lithium-containing phosphate material, and the carbon coating amount refers to the mass content of carbon.
2. The lithium ion secondary battery according to claim 1, characterized in that In the positive electrode active material, a mass content of the first lithium-containing phosphate material is greater than or equal to a mass content of the second lithium-containing phosphate material.
3. The lithium ion secondary battery according to claim 1, characterized in that In the total mass of the first lithium-containing phosphate material and the second lithium-containing phosphate material, the mass content of the second lithium-containing phosphate material is 5% to 50%.
4. The lithium ion secondary battery according to claim 2, characterized in that: In the total mass of the first lithium-containing phosphate material and the second lithium-containing phosphate material, the mass content of the second lithium-containing phosphate material is 10% to 30%.
5. The lithium ion secondary battery according to claim 1, characterized in that At least one of the following conditions is met: (1) The carbon coating amount in the first lithium-containing phosphate material is 1% to 1.3%; (2) The carbon coating amount in the second lithium-containing phosphate material is 1.3% to 1.8%; (3) The difference between the carbon coating amount in the second lithium-containing phosphate material and the carbon coating amount in the first lithium-containing phosphate material is 0.1% to 0.8%.
6. The lithium ion secondary battery according to claim 1, wherein: At least one of the following conditions is met: (1) The first lithium-containing phosphate material satisfies: 0.92 ≥ I A / I B ≥0.8; (2) The second lithium-containing phosphate material satisfies: 1.05 ≥ I A / I B ≥0.
95.
7. The lithium ion secondary battery according to claim 1, characterized in that The average primary particle size of the first lithium-containing phosphate material is greater than the average primary particle size of the second lithium-containing phosphate material.
8. The lithium ion secondary battery according to claim 7, characterized in that The ratio of the average primary particle size of the first lithium-containing phosphate material to the average primary particle size of the second lithium-containing phosphate material is 3-40.
9. The lithium ion secondary battery according to claim 1, wherein: The average primary particle size of the first lithium-containing phosphate material is 700 nm to 1500 nm.
10. The lithium ion secondary battery according to claim 8, characterized in that The average primary particle size of the first lithium-containing phosphate material is 700 nm to 1200 nm.
11. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The average primary particle size of the second lithium-containing phosphate material is 20 nm to 260 nm.
12. The lithium ion secondary battery according to claim 11, wherein: The average primary particle size of the second lithium-containing phosphate material is 80 nm to 160 nm.
13. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The aspect ratio of the second lithium-containing phosphate material is (1.1-3.9):
1.
14. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: At least one of the following conditions is met: (1) The powder compaction density of the first lithium-containing phosphate material under a pressure of 3t is 2.38 g / cm 3 ~2.68 g / cm 3 ; (2) The powder compaction density of the second lithium-containing phosphate material under a pressure of 3t is 1.85 g / cm 3 ~2.35 g / cm 3 ; (3) The compaction density of the positive electrode film layer on one side of the positive electrode sheet is 2.45 g / cm 3 ~2.8g / cm 3 .
15. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The chemical formula of the lithium-containing phosphate in the first lithium-containing phosphate material and the second lithium-containing phosphate material is Li β Fe α M (1-α) PO4, wherein 0.2≤α≤1, 1≤β≤1.1, and M includes at least one of Ti, V, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, and Sr.
16. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: In the positive electrode film layer, the total mass content of the positive electrode active material is 92% to 98%.
17. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The positive electrode film layer further includes a binder, and the positive electrode film layer satisfies at least one of the following characteristics: (1) In the positive electrode film layer, the mass content of the binder is 1% to 4%; (2) The binder includes at least one of polyvinylidene fluoride, polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyurethane, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
18. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The positive electrode film layer further includes a conductive agent, and the positive electrode film layer satisfies at least one of the following characteristics: (1) In the positive electrode film layer, the mass content of the conductive agent is 1% to 4%; (2) The conductive agent includes at least one of conductive carbon, metal fiber and organic conductive polymer.
19. The lithium ion secondary battery according to claim 18, wherein: The conductive carbon includes at least one of carbon nanotubes, graphite, graphene, carbon black, Ketjen black, carbon dots and carbon nanofibers, and the carbon black includes acetylene black.
20. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The lithium ion secondary battery also includes an electrolyte, which includes an additive, and the additive includes at least one of 1-methyl-3-[(3-trimethoxysilyl)-propyl]imidazole bis(trifluoromethanesulfonamide), 1-methyl-3-propylpyrrolidine bis(trifluoromethanesulfonic acid)imide grafted with aluminum oxide, lithium difluorobisoxalate borate, fluoroethylene carbonate and 1,3-dioxolane.
21. A positive electrode active material, characterized in that: The positive electrode active material comprises a mixture of a first lithium-containing phosphate material in a granular state and a second lithium-containing phosphate material in a rod-shaped state, wherein the first lithium-containing phosphate material and the second lithium-containing phosphate material have a diffraction peak A between 29° and 30° and a diffraction peak B between 25° and 26° in an X-ray diffraction spectrum, and the intensity ratio of the diffraction peak A to the diffraction peak B is 1:
1. A / I B ; The second lithium phosphate material satisfies: 1.1≥I A / I B ≥0.95; I of the second lithium-containing phosphate material A / I B Greater than the I of the first lithium-containing phosphate material A / I B ; Both the first lithium-containing phosphate material and the second lithium-containing phosphate material contain a carbon coating layer, the carbon coating amount in the first lithium-containing phosphate material is less than the carbon coating amount in the second lithium-containing phosphate material, and the carbon coating amount refers to the mass content of carbon.
22. The positive electrode active material according to claim 21, characterized in that The positive electrode active material is the positive electrode active material according to any one of claims 2 to 20.
23. An electrical device, characterized in that: A lithium ion secondary battery comprising any one of claims 1 to 20 and at least one of the positive electrode active materials according to claim 21 or 22.
Citation Information
Patent Citations
Negative pole piece, secondary battery, battery pack, battery module and electric device
CN116636050A
Positive pole piece, secondary battery, battery module, battery pack and electric device
CN116762192A